Social Work and Geriatric Services 2016
DOI: 10.1201/b13135-10
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Exercise in Community-Dwelling Older Adults

Abstract: Background. The decline of motor performance of the human hand-arm system with age is well-documented. While dominant hand performance is superior to that of the non-dominant hand in young individuals, little is known of possible age-related changes in hand dominance. We investigated age-related alterations of hand dominance in 20 to 90 year old subjects. All subjects were unambiguously right-handed according to the Edinburgh Handedness Inventory. In Experiment 1, motor performance for aiming, postural tremor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 63 publications
3
16
0
Order By: Relevance
“…By considering several categories of age (immature, adolescent, young and mature adult and elder), Prieur et al () and Prieur, Pika, Blois‐Heulin, and Barbu () recently showed that chimpanzees’ right‐hand use increased with age, but until the shift in elderly: older chimpanzees were less right‐handed than adolescents, young and mature adults for both non‐communication actions (use of a stick to obtain out‐of‐reach food) and gestures. A similar decrease of right‐hand use with age has been reported for humans (Kalisch, Wilimzig, Kleibel, Tegenthoff, & Dinse, ). However, as far as we know, our study was the first to evidence a possible senescence effect on non‐human primates’ manual laterality for both non‐communication actions and gestures.…”
Section: Non‐human Primates’ Manual Laterality For Manipulations and supporting
confidence: 81%
“…By considering several categories of age (immature, adolescent, young and mature adult and elder), Prieur et al () and Prieur, Pika, Blois‐Heulin, and Barbu () recently showed that chimpanzees’ right‐hand use increased with age, but until the shift in elderly: older chimpanzees were less right‐handed than adolescents, young and mature adults for both non‐communication actions (use of a stick to obtain out‐of‐reach food) and gestures. A similar decrease of right‐hand use with age has been reported for humans (Kalisch, Wilimzig, Kleibel, Tegenthoff, & Dinse, ). However, as far as we know, our study was the first to evidence a possible senescence effect on non‐human primates’ manual laterality for both non‐communication actions and gestures.…”
Section: Non‐human Primates’ Manual Laterality For Manipulations and supporting
confidence: 81%
“…To address the issue, we considered the differences in cortical activity during the 35 controlled execution of fine motor tasks between elderly adults and young adults using 36 electroencephalography (EEG). Consistent with the dedifferentiation theory [8,17], we 37 found that the motor cortex of younger adults activated much faster during the 38 dominant hand task, while in elderly adults, the time required for motor activation was 39 equal for both hands and approached the level of the non-dominant hand of younger 40 adults. Further, as expected, we found significant differences in cortical activation 41 during the time interval preceding the motor action.…”
Section: Introductionsupporting
confidence: 78%
“…immatures. This decrease in right-hand use by elderly subjects has already been documented in humans (Kalisch et al 2006). A reason might be that physical limitations and lower activity associated with ageing could decrease the practice-based performance of the right hand that would thus converge towards the performance of the left hand (humans: Hughes et al 1997;Schut 1998;Ranganathan et al 2001).…”
Section: Modulation By Signaller's Age Classmentioning
confidence: 59%